PELATIHAN PERAWATAN TRANSMISI MOTOR MATIC UNTUK MENINGKATKAN PERFORMA MOTOR DI DESA SUKAMUKTI - Widiyanto, Dimas; Sikki, M. Ilyas; Supratno, Setyo (Universitas Islam 45 Bekasi, 2024)
This service activity aims to train the community so that people can be more aware or given awareness about the maintenance of their personal vehicles, so that they are more independent in maintaining their motorbikes. Because many people only use their vehicles and don't think about maintenance, this will become a complex problem because over time, the vehicle's performance will decrease, and at any time this can have fatal consequences for the driver himself. From this problem, a solution was found by creating a motorbike maintenance training program to educate and introduce the procedures for maintaining motorbikes, especially in the automatic motorbike transmission section. The result of this activity is that residents understand more about the parts in automatic motorbike transmissions, how to maintain them, can practice the correct maintenance methods, and the dangers that arise if spare parts in automatic motorbike transmissions are not properly maintained.